Mechanisms of financing and management of financial resources in the agricultural sector in Colombia - Ossa, Jahir Alexander Gutiérrez; Giraldo, Nelson Eduardo Castaño; Mosquera, Elimeleth Asprilla (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The article notes the impact that has banking and credit versus the needs of resource for investment of the agricultural sector in Colombia. The provision of financial resources for the agricultural sector is one of the main bottlenecks. The exploratory and descriptive analyses serve as a methodological basis for the thematic development of this paper. The need for liquidity and irrigation of resources are taken as break points for the industry, and, at the same time, as the impact of the financial sector versus credit needs is not clearly known, it has been left its viability to the cyclical market conditions. Thus, the financial opening to the agricultural sector should be a constant in banking.